Histological and morphological evaluation of condylar cartilage of young rats in response to stimulation of mandibular protrusion - Milena Peixoto Nogueira de Sá; Adilson Luiz Ramos; Jacqueline Nelises Zanoni; Fabrício Dias de Souza; Daniele Esteves Pepelascov; Raquel Sano Suga Terada (Universidade Estadual de Maringá, 2017)
The aim of this study was to evaluate the histogical and morphological aspects of the condyle in response to mandibular protrusion induced by composite resin occlusal planes. Thirty five-week-old male Wistar rats were selected and randomly divided in two groups. One group received a composite resin type of oclusal plane that induced mandibular protrusion, and the other was the control group, without treatment. Animals were euthanized after experimental time intervals of 7, 21 and 30 days. For histological analysis, thickness of the proliferative, serial and hypertrophic layers was measured, as well as each layer separately. The highest difference in cartilage thickness was observed at day 21, showing a significant increase of the proliferative layer. There were also other histomorphological changes related to occlusal plane interference. Condylar forward repositioning induced by composite occlusal planes influenced the endochondral ossification, increasing the proliferative layer.